Eksperimen Material Sampah Laut Sebagai Material Pendukung Ruang Interior - Sheilly Yuliani Purnomo; Andereas Pandu Setiawan (Intra, 2019)
Environmental factors are the center of attention throughout the world. Garbage is the main cause of this problem, especially in the sea. A popular solution so far is the 3R (reduce, reuse, recycle). Recycling method is the most effective solution to deal with marine debris. The marine debris material experiment aims to find new material that can be used as interior products material. The method used in this study is to grow creativity to make as many alternatives as possible, also by applying Research and Development Method. Several stages in processing marine debris are material collection, melting, mixing of materials, printing, and finishing. The results can create various material combinations of marine debris, especially plastic based that can be used for interior design materials.